2021
DOI: 10.1253/circj.cj-20-1051
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Long-Term Evolocumab Use Among Asian Subjects ― A Subgroup Analysis of the Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk (FOURIER) Trial ―

Abstract: where there is less evidence of altered drug pharmacokinetics, including for the use of lipid-lowering agents. The efficacy of statins on low-density lipoprotein cholesterol (LDL-C) reduction at any given dose appears broadly similar among individuals of Asian vs. other backgrounds, 3 although a A sian patients are commonly treated with lower doses of pharmacological agents than are Western patients. The importance has been well documented for use of certain β-blockers and anesthetic agents, where genetic trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In this study, with 84.5% of participants at very-high cardiovascular risk, tafolecimab demonstrated a favorable risk-benefit profile, with safety profile similar to those identified in previous studies and those of alirocumab and evolocumab [ 8 , 9 , 11 , 15 , 26 ]. Serious adverse events were possibly related to underlying medical conditions of the participants, further reflecting late diagnosis of HeFH in China and high risk for cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, with 84.5% of participants at very-high cardiovascular risk, tafolecimab demonstrated a favorable risk-benefit profile, with safety profile similar to those identified in previous studies and those of alirocumab and evolocumab [ 8 , 9 , 11 , 15 , 26 ]. Serious adverse events were possibly related to underlying medical conditions of the participants, further reflecting late diagnosis of HeFH in China and high risk for cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 80%
“… 15 Recently, a sub-analysis of the Fourier trial in patients with ACS reported the safety and efficacy of evolocumab in Asians ( n = 2723) compared with individuals of other racial origins ( n = 24 841). 19 With regard to the patients’ background, myocardial infarction was significantly less prevalent in Asians than in individuals of other races, whereas diabetes mellitus and stroke were more common in Asians. Compared with individuals of other races, BMI and LDL-C levels were significantly lower among Asians, and the use of potent statins was less common in Asians (33.3% Asians vs. 73.3% other races; P < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Cases of cataracts were reported in the FOURIER and ODYSSEY OUTCOMES trials of evolocumab and alirocumab, respectively. However, more cases of cataracts were reported in the placebo group than in the study group in both trials 31–35 . The meta‐analysis of the cataracts association with statins and PCSK9 inhibitors indicated no significant effect of cholesterol‐lowering with statins or PCSK9 antibodies association with cataracts 13 .…”
Section: Discussionmentioning
confidence: 97%
“…However, more cases of cataracts were reported in the placebo group than in the study group in both trials. [31][32][33][34][35] The meta-analysis of the cataracts association with statins and PCSK9 inhibitors indicated no significant effect of cholesterol-lowering with statins or PCSK9 antibodies association with cataracts. 13 Similarly, our study found no disproportionate signal for cataracts.…”
Section: Discussionmentioning
confidence: 99%